Pengembangan Teknik Life Theatre Berbasis Teori Dramaturgi dalam Konseling Naratif Untuk Mereduksi Perilaku Antisosial Akibat Overstimulasi Digital - Lahia, Ilham; Putra, Devindra Herva Dwi (SENTRI: Jurnal Riset Ilmiah, 2025)
Digital overstimulation has become a growing psychosocial concern among adolescents, contributing to reduced empathy, impaired emotional regulation, identity confusion, and increased antisocial behavior. Continuous exposure to social media, excessive information, and rapid digital interactions often weakens adolescents' ability to establish healthy interpersonal relationships and develop positive self-identities. These challenges highlight the need for innovative counseling approaches that are creative, reflective, and relevant to the realities of the digital era. This study aimed to develop the Life Theatre Technique, a counseling innovation integrating Erving Goffman's dramaturgical theory with Narrative Counseling to reduce adolescents' antisocial behavior resulting from digital overstimulation. The study employed a literature review method by examining national and international publications published between 2015 and 2026, retrieved from Google Scholar, Garuda, DOAJ, SINTA, and ScienceDirect. Selected studies were analyzed using content analysis and thematic synthesis to identify conceptual relationships among digital overstimulation, antisocial behavior, narrative counseling, and dramaturgical theory. The findings indicate that digital overstimulation negatively affects adolescents' social competence and emotional development, while Narrative Counseling effectively reconstructs self-identity through externalization and re-authoring processes. Furthermore, dramaturgical theory provides a symbolic-reflective framework that enables adolescents to critically examine and reconstruct the social roles they perform in everyday life. The integration of these perspectives resulted in the development of the Life Theatre Technique, which positions students as the protagonists of their own life stories while externalizing maladaptive behaviors as antagonistic characters. This conceptual model has the potential to enhance self-awareness, empathy, emotional regulation, prosocial behavior, and identity reconstruction, offering an innovative and contextually relevant counseling strategy for addressing adolescents' psychosocial challenges in the digital age.